Jejak-jejak Imperial dalam Beragam Nasionalisme Asia Tenggara - Ali-Fauzi, Ihsan (Studia Islamika, 2013)
Anthony Reid, Imperial Alchemy: Nationalism and Political Identity in Southeast Asia (New York: Cambridge University Press. 2010), xiii + 248 pages.Reid has long been widely known as a senior historian with a specialty in the history of Aceh, Sumatra, and the Indonesian revolution. Recently, he has begun to write about the history of Southeast Asia. Inspired by French historian Fernand Braudel, this work presents what Reid calls a “total history” of this region. In this approach wars, royal dynasties, and foreign traders are not prioritized over the diets, health, and pastimes of ordinary people. Through this work, Reid has begun to strengthen the study of Southeast Asia. As one of the pioneers and masters of the study of Asia and the Pacific, particularly Southeast Asia, Reid is uniquely positioned to offer new insights about this region’s history. In this book, Reid offers a new understanding of the historical data collected on the link between ethnic identity, nationalism, and history of Southeast Asia.DOI: 10.15408/sdi.v20i3.516